Gambaran Tingkat Stres Kerja Perawat Rumah Sakit pada Era New Normal - Tia Oktari; Fathra Annis Nauli; Hellena Deli (STIKes Payung Negeri Pekanbaru, 2021)
Background: Work stress is one of the problem that occured inte new normal era for nurses in working adjustments due to Covid-19. This study aims to describe the level of work stress of hospital nurses in the new normal era. Methods: This research is quantitative descriptive study. The research sample was 113 respondents using total sampling technique. Data collesction used research questionaire Tayyib and Alsolami (2020) which has been modified again by researcher and carried out a validity test with a value range of 0,450-0,795 ≥ r table 0,444 and the reability test get crobac’s alpha 0,923 results with r table 0,444. Results: An overview of the work stress level of hospital nurses in the new normal era who experienced mild work stress was 30 peoples (26,5%), experienced moderate work stress 56 peoples (49,6%) and experienced severe work stress 27 peoples (23,9%). Conclusion: The majority of respondents are at a moderate level of work stress. It is hoped that the hospital management can carry out work stress management training and counseling regarding the pressures by health worker when treating patients in the new normal era to minimize the psychological problems of health worker at work.